Analisis Kesalahan Penyetoran dan Pelaporan Pajak Pertambahan Nilai Pada PT. RA - Bayu Sarjono; Siti Indriyani Nur Mahmuda (PT Naureen Digital Education, 2023)
This study discusses the cases that occurred at PT. RA, namely the error in depositing and reporting Periodic VAT Notification Letters. In February 2022 PT. RA made a mistake in depositing Value Added Tax in the amount of IDR 14,971,366 which resulted in NTPN not being able to be entered in the e-faktur. Then in March 2022, the calculation of the Value Added Tax payable is IDR 20,470,000. At the time of reporting the March 2022 Periodic VAT Notification Letter, it was discovered that there were input taxes that had not been uploaded on the e-faktur so the tax that should have been payable was IDR 16,262,139. This research method uses the case study method. The results of the study show that VAT deposit errors occur when filling in the tax year column so taxpayers must make book transfers. There was an error in the book entry made when it was discovered that the transfer letter was addressed to another party, namely PT. homework This makes PT. PR must transfer back to PT. RA. For input taxes that have not been uploaded, the input tax is prepopulated in March 2022 which results in an overpayment of IDR 4,207,861 which can be compensated in the following period. Keywords: deposit, e-faktur, Periodic Tax Return, Prepopulated Input Tax, reporting, Value Added Tax,